Mengajar dan Belajar Bahasa Inggris Menggunakan Google Classroom untuk Pelajar - Maulaniam Sholah, Hanif (LPPI Universitas Al-Qolam Malang, 2020)
Technology takes all the integral roles in our life. Not only the roles of job commercial but also the roles of teaching and learning. Online learning is a typical teaching and learning process through electronic media of computers and the internet. This system calls an E-Learning or Blended Learning. E-Learning system is the manifest of Information and Communication Technology (ICT) that currently grows up rapidly in this modern era. In this 21st era, learners require to renew the knowledge of the way for learning through any technological tools. Both teachers and students must be aware of the use of technology and how to use it in the learning process. Some advantages of learning using ICT for teachers and students are necessary to be considered. Teachers can manage the large class efficiently because technology takes the teachers' role as the media of learning. Besides, a varied assignment can give effect. Then, the teacher can access the students' responses anytime in any places and also teachers can give feedback directly. Technology provides the chance of learning not only at school but also at home or in any place. This paper focuses on the understanding of using “Google Classroom